Is There A Role of Glycated Hemoglobin for Predicting Major Ad- verse Cardiac Event in ST-Elevation Myocardial Infarction? - Muhammad Abusari; Cholid Tri Tjahjono; Dadang Hendrawan; Yoga Waranugraha; Ayu Asri Devi Adityawati; Ratna Pancasari (Heart Science Journal, 2020)
Background : Coronary Artery Disease (CAD) especially ST-Elevation Myocardial Infarction (STEMI) is the leading cause of mortality worldwide. Hyperglycemia and diabetes mellitus are both prevalent among patients with STEMI admitted to the hospital. Glycated hemoglobin (HbA1c) is a marker of glucose control.Objectives : We aimed to investigate the role of HbA1c as the predictor of major adverse cardiovascular events in STEMI patients.Methods : This was a retrospective cohort study. STEMI patients visiting Saiful Anwar General Hospital were registered. Patients were divided into three groups based on the HbA1c level <6.5%; 6.5-8.4% and ≥8.5%; respectively. The primary endpoint was in-hospital Major Adverse Cardiovascular Events (MACE), including cardiac death, recurrent myocardial infarction (MI), recurrent revascularization, acute pulmonary edema, cardiogenic shock, malignant arrhythmia, and stroke.Results: A total of 118 STEMI patients were included in this study, with distribution of 61 patients with HbA1c <6.5%, 25 patients with HbA1c 6.5-8.4%, and 31 patients with HbA1c ≥8.5%; respectively. The HbA1C level was associated with the history of diabetes mellitus (3.2% vs 36% vs 71%; p =0.000) and random blood glucose level at hospital admission (140.71 ± 39.67 mg/dL vs 172.96 ± 53.43 mg/dL vs 366.61 ± 169.67 mg/dL; p = 0.000). The MACE among three groups was not significantly different (17.7% vs 20% vs 35.5%; p=0,149). Conclusion: Our study reveals that the HbA1c level at hospital admission is associated with the history of diabetes mellitus and random blood glucose at hospital admission. However, HbA1c could not predict MACE in STEMI patients